1997
DOI: 10.1121/1.420346
|View full text |Cite
|
Sign up to set email alerts
|

Detection and discrimination of frequency glides as a function of direction, duration, frequency span, and center frequency

Abstract: The study investigated the ability to detect and discriminate frequency glides under a variety of experimental conditions. The subjects distinguished between a comparison signal that either was level in frequency or was swept across a fixed frequency span, and a target signal that changed more in frequency than the comparison signal. Tone durations were 50 and 400 ms. Nominal center frequencies were 0.5, 2, and 6 kHz; actual center frequencies were varied randomly, or roved, over a range equal to 0.1 times the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…The matches to rising glides were, on average, at frequencies slightly lower than two thirds of the way into the glide; falling glides received matches that were closer to the midpoint of 1,000 Hz. This confirms findings by Gardner and Wilson [1979], Madden and Fire [1997], Moore and Sek [1998, exper-iment 1, transition span of 0 Hz], Nábelek [1978], Pisoni [1976], Schouten [1985], and Smoorenburg and Coninx [1980], to the effect that falling tones are perceptually closer to steady-state tones than are rising ones. In all these studies, it is easier to discriminate stationary tones from rising than from falling glides, although the difference is usually small.…”
Section: Control Condition 1 (Single Matching Tone)supporting
confidence: 78%
“…The matches to rising glides were, on average, at frequencies slightly lower than two thirds of the way into the glide; falling glides received matches that were closer to the midpoint of 1,000 Hz. This confirms findings by Gardner and Wilson [1979], Madden and Fire [1997], Moore and Sek [1998, exper-iment 1, transition span of 0 Hz], Nábelek [1978], Pisoni [1976], Schouten [1985], and Smoorenburg and Coninx [1980], to the effect that falling tones are perceptually closer to steady-state tones than are rising ones. In all these studies, it is easier to discriminate stationary tones from rising than from falling glides, although the difference is usually small.…”
Section: Control Condition 1 (Single Matching Tone)supporting
confidence: 78%
“…That the auditory system, in general, is well equipped to analyze FM signals has been shown in a range of neurophysiological studies in animals (Whitfield and Evans, 1965;Suga, 1968;Heil et al, 1992;Mendelson et al, 1993;Eggermont, 1994Eggermont, , 2001Liang et al, 2002) as well as in human psychophysical (Schouten, 1985(Schouten, , 1986Dooley and Moore, 1988;Schouten and Pols, 1989;Viemeister, 1994a,b, 1997;Madden and Fire, 1997;Moore, 1997;Moore and Sek, 1992;Gordon and Poeppel, 2002) and brain imaging studies (Makela et al, 1987;Dimitrijevic et al, 2001;John et al, 2001John et al, , 2002Picton et al, 1987Picton et al, , 2003Boemio et al, 2005;Luo et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Future studies need to test if these two DF thresholds match with each other in individual CI users. Madden and Fire (1997) showed that NH listeners can detect 400-ms, 12-Hz frequency glides around 500 Hz. Although obtained with different experimental setups, these NH data were slightly lower than our CI users' DF thresholds.…”
Section: Discussionmentioning
confidence: 99%